Environmental Simulation and Behavioral Response as Means of Enquiry in Multidisciplinary Design Research Procedure - Nopadon Sahachaisaeree (My University, 2012)
The paper attempts to discuss the research methodology and research tools pertaining to physical design at all level. It starts with the definition of scientific research and its underlying obligation—on why and how empirical approach proves and derives facts to accommodate good design.. The paper also connects the field of environment and behavior with research approaches in design, assuming that design of physical environment meant to respond to users' daily living behavior, and vice versa. Simulation is thus a crucial tools for cognitive enquiry. A number of research experiences are cited to support such viewpoints.
Keywords: Design Education and Practice